''Our American Way of Living': Lucy Richardson Milligan and American Radio on the eve of World War II'. Issue 4 (1st October 2020) - Lockley, Tim
Abstract : Lucy Richardson Milligan organised a series of radio talks entitled 'Our American Way of Living' to be broadcast during the intermissions of the Metropolitan Opera broadcasts in 1940-41. She deliberately set out to counter fascist propaganda and embedded her talks within a program that had a very large audience. By doing so she co-opted one of the techniques of Nazi propagandists and did so in the year before the US entered WWII.